Thin films of Ag–Au nanoparticles dispersed in TiO2: influence of composition and microstructure on the LSPR and SERS responses - Borges, Joel Nuno Pinto (2018)
Thin films containing monometallic (Ag,Au) and bimetallic (Ag-Au) noble nanoparticles were dispersed in TiO2, using reactive magnetron sputtering and post-deposition thermal annealing. The influence of metal concentration and thermal annealing in the (micro)structural evolution of the films was studied, and its correlation with the localized surface plasmon resonance (LSPR) and surface enhanced Raman spectroscopy (SERS) behaviours was evaluated. The Ag/TiO2films presented columnar to granular microstructures, developing Ag clusters at the surface for higher annealing temperatures. In some cases, the films presented dendrite-type fractal geometry, which led to an almost flat broadband optical response. The Au/TiO2system revealed denser microstructures, with Au nanoparticles dispersed in the matrix, whose size increased with annealing temperature. This microstructure led to the appearance of LSPR bands, although some Au segregation to the surface hindered this effect for higher concentrations. The structural results of the Ag-Au/TiO2system suggested the formation of bimetallic Ag-Au nanoparticles, which presence was supported by the appearance of a single narrow LSPR band. In addition, the Raman spectra of Rhodamine-6G demonstrated the viability of these systems for SERS applications, with some indication that the Ag/TiO2system might be preferential, contrasting to the notorious behaviour of the bimetallic system in terms of LSPR response.